Fifty Years of Entomological Publications in the Revista de Biología Tropical - Hanson, Paul (Revista de Biología Tropical, 2002)
Over its fifty year history nearly twenty percent of the papers published in the Revista de Biología Tropical have been about insects and arachnids. In the 1950’s papers on arthropods of medical importance were dominant, in the 1960’s there was a poliferation of papers on bees, and in more recent years the subjects have become incresingly diverse. In terms of nationality of contributing authors, the journal appears to have become increasingly international in later years.